1993
DOI: 10.1182/blood.v82.11.3259.bloodjournal82113259
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Epstein-Barr virus-associated hemophagocytic syndrome

Abstract: A virus-associated hemophagocytic syndrome is characterized by high fever, liver dysfunction, coagulation abnormalities, pancytopenia, and a benign histiocytic proliferation with prominent hemophagocytosis in bone marrow, lymph node, spleen, and liver. We describe six Japanese children with fatal Epstein-Barr virus (EBV)-associated hemophagocytic syndrome. Five of the six patients had serologic evidence of primary EBV infection at the onset of their diseases. EBV genomes were detected in all the patients by So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
44
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 0 publications
0
44
0
Order By: Relevance
“…The majority of IM patients recover after an average febrile course of 10 d . However, EBV‐associated IM can rarely develop into a lethal hemophagocytic lymphohistiocytosis (HLH), a disorder of fulminant features such as persistent fever, cytopenia, coagulopathy and multiple organ failure . The disease course from simple IM to HLH can progress very rapidly .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of IM patients recover after an average febrile course of 10 d . However, EBV‐associated IM can rarely develop into a lethal hemophagocytic lymphohistiocytosis (HLH), a disorder of fulminant features such as persistent fever, cytopenia, coagulopathy and multiple organ failure . The disease course from simple IM to HLH can progress very rapidly .…”
mentioning
confidence: 99%
“…Patients fulfilling at least five of the eight criteria are diagnosed with HLH. However, there is increasing evidence that certain patients do not fulfil all of these criteria until the results of bone marrow biopsies are obtained . Moreover, immunological and histopathological examinations are not widely used in clinical practice and require specialists to perform and interpret.…”
mentioning
confidence: 99%
“…The clinical picture progresses with development of adenopathy, hepatosplenomegaly and cytopenias secondary to bone marrow involvement or haemophagocytic syndrome. Liver failure, multi‐organ dysfunction and death usually occur (Kikuta et al , ; Quintanilla‐Martinez et al , ). Recently, Kim et al () reported a case of an infant with EBV+LPD treated successfully with dexamethasone.…”
Section: Specific Disease Entitiesmentioning
confidence: 99%
“…Recently, Kim et al () reported a case of an infant with EBV+LPD treated successfully with dexamethasone. Outcomes are very guarded, with poor responses to different therapies including etoposide, or immunomodulation with intravenous immunoglobulins, suggesting that different therapeutic approaches are urgently needed (Kikuta et al , ; Su et al , ). It is possible that cytotoxic T cell adoptive immunotherapy, such as latent membrane protein (LMP)‐specific cytotoxic T‐lymphocytes (CTL), currently available to treat patients with EBV+ post‐transplant lymphoproliferative disease (PTLD), can be of benefit for patients with other EBV‐LPD.…”
Section: Specific Disease Entitiesmentioning
confidence: 99%
“…In young children an X-linked lymphoproliferative disorder (XLP) with fatal HS or familial haemophagocytic lymphohistiocytosis (FHL) has been documented (Caballes et al, 1997). Recently, a nonfamilial fatal HS has been reported in young children in Taiwan (Chen et al, 1991;Su et al, 1994), Japan (Kikuta et al, 1993) and Hong Kong (Wong & Chan, 1992). In the original 10 cases reported by Chen et al (1991), patients usually died after a fulminant course.…”
mentioning
confidence: 99%